Effect of sorghum genotype, germination, and pretreatment on bioethanol yield and fermentation - Yan, Shuping (Kansas State University, 2011)
Grain sorghum is the second major starch-rich raw material (after corn) for bioethanol production in the United States. Most sorghum feedstock for bioethanol production is normal non-tannin sorghum. Waxy sorghum and tannin sorghum are rarely used due to lack of scientific information about waxy sorghum fermentation performance and the way to increase fermentation efficiency of tannin sorghum. The main objectives of this study were to investigate the fermentation performance of waxy sorghum and to improve fermentation efficiency of tannin sorghum using techniques such as germination and ozonation treatments. The ethanol fermentation performance on both waxy sorghum and tannin sorghum were evaluated using a dry grind ethanol fermentation procedure. Fermentation efficiencies of tested waxy sorghum varieties ranged from 86 to 93%, which was higher than normal (non-waxy) sorghum varieties. The advantages of using waxy sorghums for ethanol production include less energy consumption, higher starch and protein digestibility, shorter fermentation time, and less residual starch in distillers dried grains with solubles (DDGS). Results from germination study showed germination significantly increased fermentation efficiency of tannin sorghum. The laboratory results were further confirmed by those from five field-sprouted grain sorghum samples. Significantly increased free amino nitrogen (FAN) contents in sprouted sorghum samples accelerated the ethanol fermentation process. Results from both laboratory-germinated and fieldsprouted samples demonstrated that germination not only increased fermentation efficiency (higher than 90%) but also reduced fermentation time by about 50%, which could result in energy saving and increased production capacity without additional investment. The excellent performance of sprouted sorghums may provide farmers a new market for field-sprouted sorghum (poor quality as food or feed) in a bad year. A previous study showed ozone had a strong connection to degradation of lignin macromolecules. The hypothesis was that ozone treatment may also reduce tannin activity and increase fermentation efficiency of tannin sorghum. Results showed that the ethanol production performance (ethanol yield, fermentation efficiency, and fermentation kinetics) of the ozone-treated, tannin sorghum flours was significantly improved compared with the untreated control. The other effects of ozonation on sorghum flour include pH value decrease, discoloration, and inactivation of tannin. In summary, these studies showed sorghum, no matter it was waxy, field-sprouted, or tannin sorghum, can be an excellent feedstock for ethanol production.
Keywords: Sorghum; Pretreatment; Bioethanol; Yield; Fermentation; Bioethanol; Agriculture, General (0473)